Struktur, Kategori, dan Fungsi Sosial Pertanyaan Tradisional (Riddles) Masyarakat Desa Pangkalan Kecamatan Pucuk Rantau Kabupaten Kuantan Singingi Provinsi Riau - Yogo Pangestu; Hasanuddin WS Hasanuddin WS (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study has the objectives of (1) describing the traditional question structure (riddles) of the Pangkalan Village community, Pucuk Rantau District, Kuantan Singingi Regency, Riau Province, (2) describing the traditional question category (riddles) for the Pangkalan Village community, Pucuk Rantau District, Kuantan Singingi Regency, Riau Province, (3 ) describes the social function of traditional questions (riddles) for the people of Pangkalan Village, Pucuk Rantau District, Kuantan Singingi Regency, Riau Province. This research is a type of qualitative research and descriptive method. This study has data on traditional questions (riddles) for the people of Pangkalan Village, Pucuk Rantau District, Kuantan Singingi Regency, Riau Province. Data collection is done in two ways, namely recording and data collection. According to the results of the study, the research results were found, namely: (1) structure, consisting of descriptive and referent elements which were classified into two categories, namely: (a) contradicting traditional questions (riddles), and (b) traditional questions ( riddles) that are not opposite (2) categories, consisting of: (a) resembling living things, (b) resembling animals, (c) resembling plants, (d) resembling inanimate objects, and (e) resembling colors, and (3 ) social functioning, which was found in the study only tested intelligence and entertainment.